Making methane gas from CO2 using Ni/Al2O3 catalyst in a fixed bed reactor - Yuliani, Tasya Dwi; Junaidi, Robert; Meidinariasty, Anerasari (Universitas Lambung Mangkurat, 2023)
CO2 emissions are one component of greenhouse gases, it is estimated that around 18.35 billion tons of CO2 are released every year (Sulistyono, 2012). This is because the world economy is recovering from the Covid-19 crisis by relying on coal. Based on IEA data, CO₂ emissions from energy combustion and industrial processes accounted for almost 89% of the energy sector's greenhouse gas emissions in 2021, while CO2 emissions from gas combustion contributed 0.7%. One way to reduce CO₂ in the atmosphere is by converting CO2 and using it into chemicals, for example hydrogenating CO2 into methane. The aim of this research is to create a fixed bed reactor for CO₂ methanation so as to reduce carbon dioxide pollution, while the research will use a Ni catalyst with alumina support (AL2O3)2. In this research, CO₂ was used as a raw material with a Ni/Al2O3 catalyst. Methane gas produced from carbon dioxide using a fixed bed reactor is a little at 1.34% Vol with a flow rate of 0.3 L/m and a concentration of 1 M to 9.25% Vol with a flow rate of 0.1 L/m and a concentration of 3 M for 60 minutes at a temperature of 55°????.